Strategi Pengembangan Produk Melalui Analisis Strength Weakness Opportunity Threat (SWOT) Pada Industri Rumahan Kerupuk Udang Kwanyar - Nurul Kamilia; Triana Setiyarini (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
This research aims to determine the description of the small shrimp cracker industry in Kwanyar District and analyze the appropriate development strategy to be applied to the shrimp cracker small industry in Kwanyar District. This research was conducted in Kwanyar Barat Village with 5 informants. The sampling technique used in this research is purposive sampling. The research instrument was conducted by interview, observation and documentation methods. The research method used is descriptive qualitative and uses swot analysis to analyze the internal and external environment of the Kwanyar Shrimp Cracker Home Business. The results show that the strategies that can be used are to produce more shrimp crackers, maintain a distinctive taste, sell at low prices, and increase promotions.